Pengaruh Penggunaan Smartphone Terhadap Perkembangan Bahasa Balita Di Wilayah Kerja Puskesmas Karang Tengah Kota Tangerang - Felda Elish; Ani Fadmawaty (Journal of Religion and Public Health, 2025)
The phenomenon of smartphone use among children has drawn attention to toddler development. This stage, which spans from 12 to 59 months, is often referred to as the "golden age" for human development. During this period, children are particularly receptive to various forms of growth, including intelligence, aptitude, physical abilities, cognitive skills, language development, social-emotional skills, and spiritual capacities. This study aims to determine the relationship between smartphone use and language development in toddlers in the working area of Karang Tengah Community Health Center, Tangerang City. This research was a quantitative study using a cross-sectional design. The study's population comprised 105 toddlers selected using a non-probability purposive sampling technique. Data analysis included univariate analysis and bivariate analysis, using the Fisher’s Exact Test. The findings reveal a p-value of 1.000 (α < 0.05), suggesting that there is no significant relationship between the level of smartphone use and language development in toddlers in the working area of Karang Tengah Community Health Center. There is no significant relationship between smartphone use and language development in toddler. For future studies, it is essential to conduct a more in-depth exploration of parenting dynamics, parental communication patterns, and the socio-economic context of families. Keywords: Smartphone use, Language development